Pengaruh Pengalaman Kerja Terhadap Kinerja Tenaga Pemasaran Karyawan PT. Hasjrat Abadi Cabang Kendari - wa yanti, wa yanti; Mustakim, Mustakim; abdullah, akhyar (Universitas Halu Oleo, 2017)
This study aims: to determine the effect of work experience on the performance of PT. Hasjrat Abadi Kendari Branch. The population in this study were all marketing staff of PT. Hasjrat Abadi Kendari Branch, amounting to 60 people using a sample of 30 marketing staff.This research was conducted by distributing questionnaires to 30 respondents and analyzed using Simple Linear Regression analysis. This model emphasizes the Effect of Work Experience on the Performance of PT. Hasjrat Abadi Kendari Branch and the analysis was processed using SPSS Version 20. The results of this study indicate that work experience has a significant effect on the performance of marketing personnel with a regression coefficient of 0.489 which means that work experience has a significant effect on the performance of marketing personnel. This can be seen from the T value of work experience obtained 4.961 with a significant value = 0,000 <0.05, which means that work experience has a significant effect on the performance of the sales force